New names for two Mexican species of Acacia (Leguminosae-Mimosoideae) - Rico Arce, Lourdes (Instituto de Ecología, A.C., 2005)
In order to complete the taxonomic treatment of Acacia for the Flora del Bajío y de regiones adyacentes two nomenclatural changes are proposed. Acacia fusicarpa L. Rico substitutes Senegalia painteri Britton & Rose and A. amabilis L. Rico substitutes S. subsessilis Britton & Rose. Additionally some comments related to the genus and its distribution in Mexico are given.